2022
DOI: 10.1126/science.add4507
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-tailed sexual contact networks and monkeypox epidemiology in the global outbreak, 2022

Abstract: The outbreak of monkeypox across non-endemic regions confirmed in May 2022 shows epidemiological features distinct from previously imported outbreaks, most notably its observed growth and predominance amongst men who have sex with men (MSM). We use a transmission model fitted to empirical sexual partnership data to show that the heavy-tailed sexual partnership distribution, in which a handful of individuals have disproportionately many partners, can explain the sustained growth of monkeypox among MSM despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 33 publications
4
140
3
Order By: Relevance
“…181 Meanwhile, using a branching process transmission model, researchers showed that a small minority of people have disproportionately large numbers of partners, which could explain the continued increase in monkeypox patients among MSM population. 182 Another research showed a transmission number of 2.43 in the MSM community among Italian cases in May-June 2022. 183 According to Endo and colleagues, 182 monkeypox’s basic reproductive number (R0) may be significantly higher than 1 over the MSM sexual contact network.…”
Section: Novel Transmission Patternsmentioning
confidence: 97%
See 2 more Smart Citations
“…181 Meanwhile, using a branching process transmission model, researchers showed that a small minority of people have disproportionately large numbers of partners, which could explain the continued increase in monkeypox patients among MSM population. 182 Another research showed a transmission number of 2.43 in the MSM community among Italian cases in May-June 2022. 183 According to Endo and colleagues, 182 monkeypox’s basic reproductive number (R0) may be significantly higher than 1 over the MSM sexual contact network.…”
Section: Novel Transmission Patternsmentioning
confidence: 97%
“… 182 Another research showed a transmission number of 2.43 in the MSM community among Italian cases in May-June 2022. 183 According to Endo and colleagues, 182 monkeypox’s basic reproductive number (R0) may be significantly higher than 1 over the MSM sexual contact network. Monkeypox virus spread model for assessing outbreak risk in a metropolitan area indicated that if transmission efficiency increases in the higher-risk group like gays and MSMs, broader populations may be affected.…”
Section: Novel Transmission Patternsmentioning
confidence: 97%
See 1 more Smart Citation
“… 21 , 22 , 23 Modelling studies have shown that dense sexual networks among men who have sex with men (MSM), particularly when there are multiple sexual partners could catalyse basic reproduction numbers above one despite relatively low secondary attack rates for MPX. 24 A recent analysis indicates that the effective reproduction number of the current outbreak is likely above one world-wide. 25 To date in the 2022 outbreak, the majority of reported MPX cases have been among individuals who identify as gay, bisexual, or MSM.…”
Section: Introductionmentioning
confidence: 99%
“…27 They also could result from the possibility that MPXV accumulated a few adaptive mutations in 2022. 28…”
Section: Figure 2 Transmission Routes Of Mpx In Animals and Humans (A...mentioning
confidence: 99%